PROTECTION OF THE WOMEN'S` RIGHTS, WHO ARE VICTIMS OF FAMILY (DOMESTIC) VIOLENCE: INTERNATIONAL PRACTICE AND NATIONAL LEGISLATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Domestic violence remains one of the most pressing social issues of our time, affecting millions of women around the world. One in three women face physical or sexual violence in her lifetime, and often within family relationships. Victims are not only the physically weak, but also women with high levels of education and social protection. This emphasizes that domestic violence has no social, economic or cultural barrier.